(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Reliability is the probability of performing the function of an item over a given period of time under the operating conditions encountered . A Fault tree analysis (FTA) is exceedingly used reliability guess tool for complex engineering systems. The classic fault tree analysis method, which contains (AND, OR) gates can efficacious build an analytical model to represent combinations of component failures that cause the failure of a system. In this paper, we analyze the fuzzy fault tree (FFT) to the qualitative analysis and quantitative analysis for the purpose of identifying the a minimal cut set and the statement of system failure through examples of complex systems (containing linking sequent and parallel). This paper includes reliability analysis as one of its basic tasks .